Pengaruh Tenaga Kerja, IPM, dan IPTIK Terhadap Ketimpangan Pendapatan di Indonesia Perspektif Ekonomi Islam - Mayasari, Ratih; Nurlaili, Nurlaili; Zulaikah, Zulaikah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Income inequality is still an important problem in Indonesia's economic development even though development continues to progress. This study aims to analyze the influence of labor, the Human Development Index (HDI), and the Information and Communication Technology Development Index (IP-ICT) on income inequality in Indonesia for the period 2018–2023 from an Islamic economic perspective. The data used is panel data from 34 provinces sourced from the Central Statistics Agency (BPS) and analyzed using a quantitative approach with the panel data regression method through EViews software. Based on the results of the t-test in this study, it is shown that partially labor has a positive and significant effect on income inequality with a probability value of 0.0140 (< 0.05). Meanwhile, the HDI variable had no significant effect on income inequality with a probability value of 0.7060 (> 0.05). The IP-ICT variable has a negative and significant effect on income inequality with a coefficient value of -0.008716 and a probability of 0.0019 (< 0.05). Simultaneously, labor, HDI, and IP-ICT have a significant effect on income inequality with an F-statistic value of 97.78723 and a probability of 0.000000 (< 0.05). From an Islamic economic perspective, income inequality is contrary to the principles of justice ('adl) and the equitable distribution of wealth as reflected in maqāṣid al-syarī'ah, so development policies need to be directed at improving the quality of labor, equitable distribution of education, and inclusive technology development to realize a fair and sustainable distribution of income.